The influence of social constraints on the quality of life of hematopoietic stem cell transplantation survivors: The chain mediating effect of illness perceptions and the fear of cancer recurrence - Shen, Zhiying; Shi, Shuangjiao; Li, Chengyuan; Ruan, Chunhong (Frontiers in Psychology, 2022)
Objective This cross-sectional correlational study aims to explore the relationship between social constraints and the quality of life of hematopoietic stem cell transplantation (HCT) survivors. Additionally, we also seek to demonstrate the chain mediating effect of illness perceptions and the fear of cancer recurrence on this relationship. Methods Convenience sampling was employed in this study. A total of 232 HCT survivors were interviewed using the Social Constraints Scale, the Brief Illness Perception Questionnaire, the Fear of Cancer Recurrence Inventory (Short Form) and the Functional Assessment of Cancer Therapy–Bone Marrow Transplant. IBM SPSS 24.0 were used for data analyses, and PROCESS macro (Model 6) was used to examine the hypothesized chain mediation model. Results A positive relationship between social constraints and quality of life verified the mediating effect of illness perceptions and the fear of cancer recurrence on this relationship. Social constraints affect the quality of life of HCT survivors via three pathways: the mediating role of illness perceptions, the mediating role of fear of cancer recurrence and the chain mediating effect of both factors. Conclusion The chain mediating effect of illness perceptions and the fear of cancer recurrence on quality of life indicates that these two variables have important practical significance with respect to improving HCT survivors’ physical and mental health. The study thus serves as a reference for health workers to improve HCT survivors’ quality of life in the future.